Tourism, Ethnicity, and Everyday Interaction in Khumbu - Shrestha, Khadga Narayan (Tri-Chandra Journal of Anthropology, 2025)
Khumbu, globally known for Mount Everest and Sherpa people, was historically a predominantly Sherpa region. However, people from other regions migrated to Khumbu in search of multiple opportunities in tourism sectors. Simultaneously, affluent Sherpas began relocating to Kathmandu, Europe and North America. The immigration of non- Sherpas and out-migration of Sherpas not only altered the demographic composition but also made Khumbu a multicultural community which led to change their everyday interaction. This paper argues that the increasing participation of non-Sherpa in Tourism of Khumbu has not only supplemented this sector but also challenged and questioned the Sherpa’s legacy and monopoly in the tourism. The paper also focuses on how Sherpas and non-Sherpas interact with each other through their ethnic based organizations. Based on the ethnographic field work: unstructured interviews and observation, the paper explores that both Sherpas and non-Sherpas have established their ethnic based organizations for maintaining ethnic identity. The organizations work as joint power and strengths of each ethnic groups. Simply, the organizations are social and cultural in nature but they are not limited within the given frame, most importantly the power and authority is embodied within them. I argue that the ethnic based organizations not only support the needs of each ethnic groups but also managed the interethnic relations and multiple identities with bargaining, exercising and balancing the power and authority within Sherpa and non-Sherpa groups in Khumbu.